Uterine natural killer cells: Time for a re-appraisal? [version 1; peer review: 2 approved] - Judith N. Bulmer; Gendie E. Lash (F1000Research, 2019)
The presence of unusual natural killer cells in human endometrium has been recognized for 30 years, but despite considerable research effort, the in vivo role of uterine natural killer (uNK) cells in both normal and pathological pregnancy remains uncertain. uNK cells may differentiate from precursors present in endometrium, but migration from peripheral blood in response to chemokine stimuli with in situ modification to a uNK cell phenotype is also possible. uNK cells produce a wide range of secretory products with diverse effects on trophoblast and spiral arteries which may play an important role in implantation and early placentation. Interactions with other decidual cell populations are also becoming clear. Recent evidence has demonstrated subpopulations of uNK cells and the presence of other innate lymphoid cell populations in decidua which may refine future approaches to investigation of the role of uNK cells in human pregnancy.